Singlet fission initiating organic photosensitizations - Takao Tsuneda; Tetsuya Taketsugu (Scientific Reports, 2024)
Abstract The feasibility of singlet fission (SF) in organic photosensitizers is investigated through spin-flip long-range corrected time-dependent density functional theory. This study focuses on four major organic photosensitizer molecules: benzophenone, boron-dipyrromethene, methylene blue, and rose bengal. Calculations demonstrate that all these molecules possess moderate $$π$$ π -stacking energies and closely-lying singlet (S) and quintet (triplet–triplet, TT) excitations, satisfying the essential conditions for SF: (1) Near-degenerate low-lying S and (TT) excitations with a significant S–T energy gap, and (2) Moderate $$π$$ π -stacking energy of chromophores, slightly higher than solvation energy, enabling dissociation for triplet-state chromophore generation. Moreover, based on the El-Sayed rule, intersystem crossing is found to simultaneously proceed at very slow rates in all these photosensitizers. This is attributed to the fact that the lowest singlet excitation of the monomers partly involves $$nπ ^*$$ n π ∗ transitions alongside the main $$π π ^*$$ π π ∗ transitions. The proposed mechanisms are strongly substantiated by comparisons with experimental studies.